Analisis Kebakaran Hutan dan Lahan dalam Hubungannya dengan Alih Fungsi dan Pengunaan Lahan di Sekitar Desa Gandang Barat Kabupaten Pulang Pisau Provinsi Kalimantan Tengah - Meichia Meichia; Muhammad Ruslan; Hamdani Fauzi; Kissinger Kissinger (EnviroScienteae, 2021)
The policy of take over the function of land in Pulang Pisau Regency are to fulfill many purposes and in the corporation scale its to become increasing income of the regency from this sector. The exploitation of the areal that using the meters of plantation / agriculture / other function tend to make a change of the macro and micro waters, that is because of Pulang Pisau Regency is peatlands that very sensitive to the need of water absorption. Gandang Barat Village which is in district of Maliku, Pulang Pisau Regency, which is directly adjacent with areal of oil palm plantation, have more high vulnerability of the fire forest and land. The using of land in this village including residentials area about 132, 5 Ha and farming about 180 Ha, oil palm plantation and plasma about 312 Ha.The method of this research is descriptive method and the sampling using purposive sampling which is analysis data of vulnerability level of fire system or Fire Risk system and using SIDIK which give more valid data and information using the SIDIK.The result of the identification of determination of cause of fire forest and land which connection between takeover function of land and using of land in society are: fire of land and forest which occurs in 2015 (with special analysis and observation fields) are occurs because of the opening land to prepare of plant oil plantations. There is about ± 284 Ha have been burns in fire. The motivation of conversion the land from agriculture / rice fields to become oil palm plantation with tiny scale more of because of the condition of the land in 2015 are bush and galam plants which about ± 284 Ha. The recommendation of decreasing fire forest and land are to determine the activity of opening land for plantation without burning the land (PLTB) which is to allocated the tools and help for opening the land and giving the production for diversify agre culture and technical guidance to increasing the productivity of plantations, and giving help for diversify of economic society. One of them is giving grants and using Pijam equipment for land preparation from the agriculture agency; Therefore to increasing the power of society specialty of Gandang Barat Village or social institutions which is to empowering of social awareness of the people in Gandang Barat Village about the loss and the dangerous of fire forest and land and also to educate of the farmers in management of prevention about fire forest and land. One of them is the formation and strengthening of community groups who care about the fire of Gandang Barat Village. In areas prone to forest and land fires, infrastructure that is adaptive to forest and land disasters can be developed, such as in the village of Tumbang Nusa, a footbridge is built using precast Cor Benton so that in the season of forest and land fires, it can still survive. Thus we recommend to increasing of management data special series that contain of information about technology, alarm, early detection and the management of preparation to face the fire forest and land.